Efektivitas Program Pelatihan Profesional Guru SD Dalam Meningkatkan Keterampilan Mengajar - Manjakani, Anggun (CV. SINAR HOWUHOWU, 2024)
This study aims to analyze the effectiveness of a professional training program for elementary school teachers in improving teaching skills. The training program focuses on developing pedagogical competence, the use of educational technology, and classroom management. This research employs a quasi-experimental design with two groups: an experimental group that participates in the training and a control group that does not. Data were collected through teaching skills tests, classroom observations, and training satisfaction questionnaires. The results show that the experimental group experienced significant improvement in teaching skills compared to the control group. These findings indicate that professional training is effective in enhancing the competence of elementary school teachers, ultimately contributing to the improvement of classroom learning quality.